Citra Merek, Nilai Persepsi, Kesadaran Merek, Kepercayaan Nasabah, dan Loyalitas Nasabah pada Perbankan Syariah - Roni Andespa; Yulia Hendri Yeni; Yudi Fernando; Dessy Kurnia Sari (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2023)
This article investigates the impact of brand image, perceived value, and brand awareness variables on customer trust and loyalty in a framework not examined by previous researchers. This study analyzes the direct and indirect effects of brand image, perceived value, and brand awareness on customer loyalty, with customer trust as a mediating variable. The study was conducted by distributing questionnaires to 500 randomly selected West Sumatra, Indonesia respondents. This study uses SEM-AMOS. The first finding of this study is that brand image, perceived value, and brand awareness directly affect the trust of Islamic bank customers. The second finding of this study is that brand image, perceived value, and brand awareness directly and indirectly affect customer loyalty, with customer trust as a mediating variable. The suggested managerial contribution is that Islamic bank managers in Indonesia must identify the factors influencing customer trust and loyalty. The suggested managerial contribution is that Islamic bank managers in Indonesia must identify the factors influencing customer trust and loyalty.